The Migration of the Warming Center and Urban Heat Island Effect in Shanghai During Urbanization - Shen, Zhongping; Shi, Jun; Tan, Jianguo; Yang, Hanwei (Frontiers in Earth Science, 2020)
Abstract: Urbanization leads to many negative climatic and environmental issues, such as urban heat island, environment pollution, and species extinctions. Based on the monthly air temperature data from 11 national meteorological stations in Shanghai, the construction land areas from 1980 to 2015 which derived from the satellite remote sensing TM image and population density of each district in Shanghai, the migration of urban warming center and its relationships with the expansion of construction land area and the increase of population density were analyzed in Shanghai. The temporal and spatial variations of urban heat island(UHI) were investigated as well. The results showed that the location of warming centers changed with the acceleration of urbanization since the 1980s. It migrated from Baoshan to Pudong and then moved towards Songjiang and Nanhui. The shifting of urban warming centers were highly related to the growth of construction land area and population density. The warming centers in all decades were located in the areas with the fastest development of construction land and population density. The air temperature in Shanghai increased significantly during 1961-2017 due to global warming and regional urbanization, and the intensity of UHI displayed three stages successively: slow growth, rapid growth, and obvious deceleration. The intensity of UHI in winter was stronger than that in summer, and it was greater in the nighttime than that during the daytime. With the accelerating process of urbanization, the UHI in Shanghai gradually expanded from the urban areas to the surrounding suburbs and even began to expand radially towards the southwest of rural areas in the 21st century. The results can provide references for urban heatwave prediction and mitigation of the UHI effect in Shanghai.